Rise of the Robots: Is Artificial Intelligence a Friend or Foe to Nursing Practice?. Issue 3 (July 2020) - Watson, Daniel; Womack, Joshua; Papadakos, Suzanne
Abstract : Much like other aspects of health care, nursing has become increasingly saturated with technology over the past several decades. Existing technology has advanced nursing in many ways and contributed to patient safety but at the cost of decreasing nurse-patient interaction. As health care technology progresses to the inclusion of artificial intelligence (AI), the future impact on nursing and direct patient care remains largely unknown, unexplored, and difficult to predict. This article aims to explore the relevance of nursing in a technologically advanced postmodern health care system. The relevance of nursing in the future is solidified by the unique nature of nursing that includes the embodiment of human caring and emotional intelligence. Nurses' abilities to intervene before patient deterioration, care for patients holistically, and manage various aspects of care will be heightened by the adoption of AI. Nurses should embrace AI technology, as we predict that it will decrease nurse workload and cognitive overload and allow for increased patient-nurse interaction. Current and future nurses should take the lead on determining how it augments nursing practice.